2014
DOI: 10.1097/pai.0b013e31829bebf6
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of ERα, ERβ, and TFF1 in Type I and II Ovarian Tumors

Abstract: Surface epithelial tumors of the ovary are no longer considered as a single disease but are divided into types I and II on the basis of their molecular features, cell of origin, and their behavior. A possible direct action of gonadal steroids on ovarian carcinogenesis has been suggested. The current information about the possible role of TFF1 in ovarian tumors,, together with its relationship to the estrogen receptor (ER) status, is insufficient. The aim of this study was to investigate ERα, ERβ, and TFF1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Many studies have concluded that the expression ratio between ER-α and ER-β determines the direction of response to oestrogens [27, 37, 38]. Thus, ER-α- and ER-β-selective agonists are promising new approach for treating specific conditions associated with endocrine-related disease [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have concluded that the expression ratio between ER-α and ER-β determines the direction of response to oestrogens [27, 37, 38]. Thus, ER-α- and ER-β-selective agonists are promising new approach for treating specific conditions associated with endocrine-related disease [25].…”
Section: Discussionmentioning
confidence: 99%
“…Park et al ., (2008) [ 29 ] found that E2 triggered the metastatic behaviours exclusively through an ER-α-dependent pathway, but ER-β had an opposing action on ER-α in ovarian cancer. Many studies have concluded that the expression ratio between ER-α and ER-β determines the direction of response to oestrogens [ 27 , 37 , 38 ]. Thus, ER-α- and ER-β-selective agonists are promising new approach for treating specific conditions associated with endocrine-related disease [ 25 ].…”
Section: Discussionmentioning
confidence: 99%